Education on the dangers of smoking among adolescents: An intervention study at SMPN 191 West Jakarta - Eff, Aprilita Rina Yanti; Eden, Yonatan; Yuliana, Anna; Abdurrasyid, Abdurrasyid (Universitas Muhammadiyah Magelang, 2025)
Smoking among adolescents is a pressing public health issue, considering its serious impact on physical and mental health during the developmental period. This community service activity aimed to increase knowledge, foster anti-smoking attitudes, and equip students with skills to refuse cigarettes. This intervention was conducted through socialization and education methods involving 90 students at SMPN 191 West Jakarta, followed by an evaluation. Initial evaluation results showed high risk factors in the students’ environment: 68.89% had smoking family members, 51.11% had been offered cigarettes by friends, and 8.89% of students admitted to having tried smoking. After the education was provided, the evaluation results showed that all students had a good understanding of the dangers of smoking and stated they would refuse if offered cigarettes. It was concluded that education and socialization are effective in increasing students’ knowledge and awareness. However, external risk factors such as family and peer influence remain a challenge, thus requiring sustained collaboration between the school, families, and the community.